Multicomponent Reactions and Multicomponent Cascade Reactions for the Synthesis of Sequence‐Controlled Polymers. Issue 23 (31st July 2018) - Zhang, Ze; You, Yezi; Hong, Chunyan
Abstract: Control over the monomer sequence during polymerization has attracted great attention in polymer science, but it remains a serious challenge. Recently, multicomponent reactions have been playing a significant role in the synthesis of sequence‐controlled polymers due to their inherent advantage of combining three or more starting materials in time‐saving, one‐pot operations to afford complex microstructures. In this feature article, the recent representative developments in the synthesis of sequence‐controlled polymers by multicomponent reactions are highlighted to give insight on the design of novel sequence‐controlled polymers with sufficient molecular diversity and complexity. The main part of this article is divided into three sections according to the different polymerization strategies using multicomponent reactions: direct multicomponent polymerization, multicomponent cascade polymerization, and iterative multicomponent reaction, respectively. It is anticipated that this feature article may provide some guidance for the fabrication of sequence‐controlled polymers by multicomponent reactions. Abstract : Multicomponent reactions play a significant role in the synthesis of sequence‐controlled polymers due to their inherent advantage of combining three or more starting materials in time‐saving, one‐pot operations. The recent representative developments in the synthesis of sequence‐controlled polymers by multicomponent reactions are highlighted in this feature article to give insight on the design of sequence‐controlled polymers with sufficient molecular diversity and complexity.